Suppression Effect of Eurycomanone on the Growth of Human Hepatoma Cells (Hepg2) by Inducing P53-Mediated Apoptotic Pathway - Zakaria, Yusmazura (2009)
Eurycomanone is a compound found in Eurycoma longifolia Jack and has been reported that it had a cytotoxic effect against various cancer cell lines. The aim of this study was to isolate eurycomanone from the roots of E. longifolia, investigate the cytotoxicity against human hepatoma cell line, HepG2, and determine the mode of action. In vivo study using nude mice as an animal model was also carried out to further confirm the ability of eurycomanone in liver cancer suppression. Eurycomanone was extracted from the roots of E. longifolia. The methanol extract was partitioned with diethylether, saturated with water. The aqueous soluble portion was further partitioned with butanol (BuOH) and water. The BuOH-soluble portion was subjected to silica gel column chromatography, TLC and finally HPLC to afford eurycomanone. The anti-proliferation assay was carried out using the MTT Cell Proliferation Assay. The cells were treated with crude extract of E. longifolia (CE) and eurycomanone at increasing concentrations for 72 hours. The findings showed that CE inhibited cell proliferation towards human malignant melanoma cell (HM3KO), human cervical cancer cell (Hela), human liver cancer cell (HepG2) and human ovarian carcinoma cell (CaOV3) with an IC50 of 60±0.25 μg/ml, 60±0.25 μg/ml, 45±0.15 μg/ml and 79±0.16 μg/ml respectively. The extracts did not inhibit the cell proliferation for both normal cell lines used, human normal skin cell (CCD11114sk), and human normal liver cells, Chang’s liver. The activity of eurycomanone towards HepG2 gave an IC50 of 3.8±0.12 μg/ml and significantly increased apoptosis in HepG2 cells. Eurycomanone also showed less toxicity towards both normal liver cells, Chang’s liver (17±0.15 μg/ml) and WLR-68 (20±0.22 μg/ml) as compared to tamoxifen (1.4±0.31 μg/ml) and vinblastine sulfate (4.2±0.37 μg/ml). In vivo study confirmed the effect of eurycomanone in the inhibition of tumor growth. Nude mice were inoculated with HepG2 cells, subcutaneously in the right flank. When the tumor volume reached 100 mm3, eurycomanone (6 mg/kg and 17 mg/kg) was applied intraperitoneally once a day, for 30 days. CE was also administered to the mice bearing tumor to compare the effectiveness between both of them. Data showed that tumor size in mice treated with eurycomanone was significantly reduced at concentration of 17 mg/kg compared to control and CE. Relative tumor growth ratio (TC) was calculated with percentage value of 39.9% and relative tumor volume (RTV of 1.5±0.09 was recorded. Growth reduction was associated with significantly reduced mitotic index. Hoechst 33258 staining was carried out in vitro, to prove the presence of apoptosis in HepG2 cells treated with eurycomanone (5 μg/ml). The characteristics of apoptosis including chromatin condensation, DNA fragmentation and apoptotic bodies were found following eurycomanone treatment. Further investigation on the cell cycle progression in HepG2 cells under eurycomanone treatment using a flow cytometry approach with PI staining was done. The cell cycle distribution was examined at various times and indicated doses. Vinblastine sulfate and genistein were used as a positive control. Eurycomanone appeared to affect processes that could inhibit the cell proliferation by inducing G2/M arrest in a time-dependent manner in HepG2 cells, with 39.9% of cells accumulated in G2/M phase. Flow cytometry with annexin-V/propidium iodide double staining was carried out to further confirm that eurycomanone induced apoptosis in HepG2 cells. Eurycomanone was shown to induce apoptosis in HepG2 cells in a time-dependent manner. After 72 hrs of exposure, only 5.6% cells were alive indicating that almost all of the cells underwent apoptosis. In the quadrant of annexin V+/PI-, 74.1% of the cells were detected. Increased cell population was observed at late apoptotic quadrant with a percentage of 15.3%. The protein expression of Bcl-2, Bax, p53 and cytochrome C were studied via flow cytometry in order to find the mechanism of action of eurycomanone. This study found that the apoptotic process triggered by eurycomanone involves the up-regulation of p53 tumor suppressor protein. The increased of p53 was followed by an increase of pro-apoptotic Bax and decrease of anti-apoptotic Bcl-2. Active Bax and inactive Bcl-2 induced the level of cytochrome C which leads to apoptosis. In conclusion, this present study indicated that eurycomanone has cytotoxic effect towards HepG2 cells. In vivo study suggested that eurycomanone has a high potential in inhibiting solid tumor growth in mice. These findings also concluded that the anticancer effect of eurycomanone against HepG2 cells was via inducing apoptosis through the up-regulation of p53 and Bax, and down-regulation of Bcl-2 which increased the levels of cytochrome C.